Surgery for Superior Cerebellar Artery Aneurysm - Mohd Zamri, Sarah Atiqah; Hamzah, Nurfaten; Jayaraman, Thinesh Kumaran (Malaysian Journal of Medical Sciences, 2025)
Background: Superior Cerebellar Artery (SCA) aneurysms account for about 1% to 3% of all intracranial aneurysms. SCA has an interesting anatomy, with multiple options of surgical approaches. Methods: From January 2022 to May 2023, a total of 167 aneurysm cases were treated at our centre. Only two patients were confirmed to have SCA aneurysm from cerebral angiography. Demographic study, clinical characteristics, radiological data, treatment plan and outcome were analysed. Results: The total number of vascular cases at our centre from January 2022 to May 2023 is 241. There were 167 cases of aneurysm (69.3%), where 115 patients (68.9%) went for surgery, and 52 (31.1%) opted for endovascular intervention. The distribution of aneurysms by location are ACA 7.2%, ACOM 24.6%, MCA 8.9%, PCOM 18.6%, ICA 21.6%, SCA 1.2%, PCA 1.8%, PICA 8.4%, vertebral artery 2.4%, and basilar artery 5.3%. Complex aneurysms made up 58.7% of all cases and were treated with endovascular procedures more often than simple aneurysms (36.7% vs. 23.2%, P = 0.04). Most patients in both the surgical and endovascular groups had good recovery outcomes (79.1% and 76.9%, respectively; P = 0.78). Both patients with SCA aneurysms were managed surgically. Two sample cases are presented: i) a proximal saccular SCA aneurysm treated with pterional craniotomy, transylvian approach, and clip reconstruction; and ii) a mid-SCA fusiform, multilobulated aneurysm managed with temporal craniotomy, subtemporal approach, Superficial Temporal Artery (STA)–SCA bypass, and excision of the aneurysm. Conclusions: SCA aneurysms are rare and present significant surgical challenges due to their complex anatomy. Choosing the right surgical approach depends on the aneurysm’s location along the SCA segments. With proper technique and surgical experience, microsurgical treatment can offer favourable outcomes for patients.